1986
DOI: 10.1002/ijc.2910380406
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody G 250 recognizes a determinant present in renal‐cell carcinoma and absent from normal kidney

Abstract: This report describes a monoclonal antibody designated G 250, subclass IgGl, that recognizes an antigen preferentially expressed on cell membranes of renal-cell carcinoma cells (RCC) and not expressed in normal proximal tubular epithelium. G 250 antibody reacted with 46 of 47 primary RCC, with 7 of 8 RCC metastases and with a few other malignant tumors. The staining pattern of G 250 differs from that of other RCC-related antibodies described. Preliminary experiments show that this antibody can be used to visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
220
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(223 citation statements)
references
References 13 publications
2
220
0
1
Order By: Relevance
“…Thus, we decided to implement our Ab-mediated gene targeting method 7,8 by using G250 mAb, which recognizes a TAA in 95% and 60% of primary or metastatic human RCCs, respectively. 17 The extensive study of this mAb, including two phase I clinical trials, revealed no adverse reactions in the patients treated and showed that G250 mAb was concentrated in RCC tumors after intravenous injections. 18,19 These findings suggested that G250 TAA could be a suitable candidate for cell targeting and gene delivery.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, we decided to implement our Ab-mediated gene targeting method 7,8 by using G250 mAb, which recognizes a TAA in 95% and 60% of primary or metastatic human RCCs, respectively. 17 The extensive study of this mAb, including two phase I clinical trials, revealed no adverse reactions in the patients treated and showed that G250 mAb was concentrated in RCC tumors after intravenous injections. 18,19 These findings suggested that G250 TAA could be a suitable candidate for cell targeting and gene delivery.…”
Section: Discussionmentioning
confidence: 93%
“…17 A suspension of 5 ϫ 10 5 cells was incubated with G250 mAb, washed three times in cold phosphate-buffered saline (PBS), and subsequently incubated with fluorescein isothiocyanate (FITC)-goat (FabЈ) 2 anti-mouse IgG. The isotype-matched mAb NKTA (IgG1 against T-cell receptor-␣␤ clonotypic determinant) (kindly provided by Dr. Thierry Hercend, Villejuif, France) was used as a negative control.…”
Section: G250 Immunophenotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although initially referred to as MN antigen, it was shortly thereafter identified as a new carbonic anhydrase by the same group (2) and was confirmed to be identical to the tumor marker G250 (named after the antibody with which it was identified) published by Oosterwijk and colleagues (3).…”
Section: Introductionmentioning
confidence: 98%
“…To date only a small number of aberrantly expressed proteins have been associated with RCC. Some of these, such as G250, are cell surface proteins that have been identified by murine Mab (Oosterwijk et al, 1986). Clinical trials are already underway utilising a number of immunotherapeutic modalities targeting the G250 protein in RCC (Lamers et al, 2002;Bleumer et al, 2004).…”
mentioning
confidence: 99%